Optimized solvents for the maceration of phenolic antioxidants from Curcuma xanthorrhiza Rhizome using a simplex centroid design - Waras Nurcholis; Nelly Marliani; Rayandra Asyhar; Minarni Minarni (Wolters Kluwer Medknow Publications, 2023)
Background: Curcuma xanthorrhiza Roxb., from the Zingiberaceae family, is a famous plant native to Indonesia that is highly effective in treating diseases due to the various chemical compounds it contains. Objective: This study aims to optimize the extraction process for the phenolic content, with its antioxidant activity, from the rhizome of C. xanthorrhiza using different solvent (water, acetone, methanol, and ethanol) systems based on the simplex centroid design using the Design Expert 13.0 program. Methods and Material: Total phenolic content (TPC) was analyzed by colorimetry using Follin-Ciocalteu, while the antioxidant activity was measured based on 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and ferric reducing antioxidant power (FRAP) using a spectrophotometer. Results: To measure TPC and DPPH, a special cubic model was used; to measure FRAP, a linear model was utilized. Each model demonstrated a good match with the R2 values for TPC (0.9808), DPPH (0.9583), and FRAP (0.7872). The combination of a mixture of water (0.409), acetone (0.307), and methanol (0.284) with a desirability level of 0.723, resulted in a TPC of 34.112 mg gallic acid equivalent (GAE)/g dry weight (DW), DPPH of 26.533 μmol Trolox equivalent (TE)/g DW, and FRAP of 92.353 μmol TE/g DW. This showed a high extraction efficiency which was optimal. Conclusions: The best condition to extract the rhizomes of C. xanthorrhiza was a ternary combination of solvents including water, acetone, and methanol in the proportions of 0.409, 0.307, and 0.284, respectively, with a desirability level of 0.723.